ACTIVITY, MECHANISM OF ACTION, AND STANDARDIZATION OF WATER KEFIR AS A HEPATOPROTECTIVE AGENT - Aligita, Widhya
Liver disease is included in the global burden of mortality and disease. In 2018, an estimated 4.5 million adults diagnosed with liver disease, resulting in nearly 2 million fatalities annually on a global scale. Hepatic fibrosis arise due to prolonged inflammation of the liver, which is associated with alterations in the gut microbiota, or dysbiosis. The significance of intestinal dysbiosis in liver health was manifested by its impact on the composition of microbial products, leading to intestinal inflammation and damage to the intestinal barrier. Currently, liver transplantation is the only treatment that can completely cure end-stage cirrhosis. Water kefir is a fermented drink made up of different kinds of bacteria and yeast that form complex biofilms inside a polysaccharide matrix. Water kefir has been empirically used to maintain health and treat various diseases, including liver disease. Nevertheless, the extent to which water kefir from Indonesia exhibits hepatoprotective properties remains mostly uninvestigated in academic research. Several studies have demonstrated the presence of antioxidant and antiinflammatory properties in water kefir, along with its potential as a hepatoprotective agent. Nevertheless, a detailed investigation of the activity and mechanism of action of water kefir as a hepatoprotective agent, particularly focusing on water kefir grain sourced from Indonesia, has not yet been conducted. The primary objective of this study was to investigate the hepatoprotective properties of water kefir in animal. Additionally, this research attempts to elucidate the underlying mechanism of action of water kefir as a hepatoprotective agent both in vivo and in silico. Preliminary investigations were conducted to ascertain the optimal composition of water kefir as a hepatoprotective agent. Water kefir was produced by fermenting water kefir grains in a sucrose solution for 48 hours. Two formulations were being compared in this study: the basic and the concentrated modified formula. Subsequently, both formulae were subjected to experimentation on rats with acute liver injury caused by CCl4. Based on the preliminary results, the animal model that underwent liver injury was used to conduct in vivo hepatoprotective activity evaluations induced with CCl4. The parameters assessed in this study were blood biochemical markers, including SGOT and SGPT, as well as liver histological examination. Additionally, the levels of proinflammatory cytokines, such as TNF-? and TGF-?, were determined. In order to enhance comprehension of the mechanism of action, an in silico computational methodology was employed. This involves conducting molecular docking simulations and protein-protein docking analyses. The process of standardizing water kefir involved the assessment of several parameters, such as pH level, lactic acid concentration, ethanol concentration, and total plate count for bacteria and yeast. The identification of the composition of microorganisms was accomplished through the utilization of PCR. According to the preliminary evaluation, it had been observed that water kefir produced using a basic formula had more potent hepatoprotective properties compared to concentrated water kefir. This was evident from the lower levels of SGOT and SGPT observed in the former. Consequently, the basic formula was chosen for subsequent experimentation. The analysis of microorganisms in water kefir led to the identification of several bacterial and yeast species, such as Lacticaseibacillus paracasei, Acetobacter indonesiensis, Acetobacter peroxydans, and Gluconacetobacter dulcium. The presence of Gluconacetobacter dulcium had never been identified in another water kefir studies. The identification of two yeast species, namely Brettanomyces bruxellensis and Candida duobushaemulonis, was also observed. The approach to producing liver disease involved the repeated administration of CCl4. The administration of curcuma extract as a standard drug and various doses of water kefir for a duration of 2 weeks resulted in a significant reduction in the levels of SGOT and SGPT, along with a decrease in TNF-? level. A liver histological examination revealed that the liver condition significantly improved following treatment with water kefir and curcuma extract. Molecular docking studies offered valuable insights into the molecular interactions occurring between metabolites and the protein targets NF-?B and Nrf2. Several metabolites exhibited larger binding free energies compared to curcumin, as a reference compound, in relation to NF-?B, while none showed more potency against Nrf2 Keap1 than curcumin. It had been observed through protein-protein docking simulation that several extracellular enzymes possessed considerable potential for interaction with the protein targets NF-?B and Nrf2. The strongest interaction was observed between DNase1 and both of these protein targets. Based on these result, it was concluded that water kefir at various concentrations could improve liver damage. The mechanism of water kefir's hepatoprotective action was to reduce the level of inflammation, which was indicated by a decrease in TNF-? levels in in vivo evaluation and a strong interaction of metabolites with the NF-?B receptor in in silico evaluation. In silico evaluation revealed that water kefir was expected could stimulated the endogenous antioxidant formation pathway as indicated by the strong interaction of metabolites and microorganism proteins with the Nrf2 receptor. Ultimately, administration of water kefir would reduce the level of necrosis as indicated by improvements in the liver histology profile. The evaluation of several probiotic strains, including those bacteria found in the present study, demonstrated favorable outcomes in enhancing liver conditions. Typically, the microbial composition of water kefir consisted of lactic acid bacteria, acetic acid bacteria, and yeast. Nevertheless, it was important to note that water kefir grain obtained from various sources might exhibit variations in the microbial composition, both in terms of quality and quantity. This study revealed the presence of Gluconacetobacter dulcium bacteria, a species that was not detected in water kefir previously, according to prior research. While the research on the hepatoprotective effects of water kefir was not as extensive as that of other fermented products, a number of studies conducted on water kefir had showed encouraging findings. According to the findings of this study, it had been observed that Indonesian water kefir possesses the capability to diminish oxidative stress levels and stimulate the pathway responsible for the production of endogenous antioxidants. Consequently, this might lead to a reduction in necrosis and fibrosis levels, thereby indicating the considerable potential of Indonesian water kefir as a hepatoprotective agent. Water kefir, as a probiotic, exhibits an additional mode of action as a hepatoprotective agent by enhancing the state of the gut microbiota. Additional investigation is required in order to validate this statement.